Ayurvedic Management of Bullous Pemphigoids (International Journal of Ayurveda and Pharma Research, 2025)
Bullous pemphigoid is a rare skin disease that causes large fluid filled blisters. They often appear on the skin near creases or armpit, upper thigs etc. The affected areas may be painful and usually very itchy. It occurs when the immune system attacks the layer of skin. the reason for the immune system attack not well understood. Here we report a case of bullous pemphigoids with a history of poor sanitary practices which can be correlated to Garajanya visarpa (Spreading condition from artificial poison) in Agadatantra (toxicology) preview, Patient presented with reddish hyper-thickened lesion with intense itching over both foot and finger webs of bilateral upper limb. Here the treatment planned according to the diagnosis, special yoga mentioned for Visarpa (spreading skin disease) and Lūta viṣa cikitsa (spider poisoning) were employed in the present case. Malayalam Viṣha cikitsa grandhas (Malayalam toxicological texts) like Prayoga samucchaya, Kriyākoumudi and Viṣavaidya jyotsnika are mentioned some the peculiar yoga are also helps to manage the case. Treatment for Gara (artificial poison) and Rasayana chikitsa (rejuvenating therapy) are also employed here. The patient got complete relief from the symptoms. In the management of bullous pemphigoids, Viṣa visarpa (spreading skin disease from poison) and Lūtaviṣa cikitsa are found to be effective.